The effect of dental and oral nursing care on knowledge of dental and oral hygiene and tooth brushing skills in inpatiens in the hospital ward in rsud bayu asih purwakarta in 2020 - Idah - Rahmah; Emma Kamelia; Hadiyat Miko (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Semarang, 2021)
ABSTRACTFor the period 2018–2019, there were 176 inpatients who were control at the dental and oral clinic. They are given oral hygiene care in the form of irrigation/spooling due to the accumulation of food debris that sticks to the tooth surface due to decreased dental and oral hygiene. The research objective: to determine the effect of dental and oral nursing care on knowledge of dental and oral hygiene and tooth brushing skills in hospitalized patients in the internal disease ward at Bayu Asih Hospital Purwakarta in 2020. The level of knowledge was measured using a questionnaire and brushing skills with direct observation by the researcher in accordance with the steps of brushing the combined technique issued by the WHO. Dental and oral nursing care was carried out for 10 days by providing counseling and brushing skills once in two days. Research method: The study was conducted during the period September to October 2020, a quasi-experimental research method with a one group pre and post test research design before and after being given oral and dental nursing care. Purposive sampling samples with inclusion criteria totaled 41 patients. Data analysis using univariate and bivariate. Results: univariate analysis that before being given dental and mouth nursing care, it was shown that 80.4% of respondents had less knowledge and after being given dental and oral nursing care find 48.8% of respondents had good knowledge, it suggest that there was an increase in knowledge of dental and oral hygiene and brushing skills before and after being given dental and oral nursing care. The finding of the research indicated that bivariate analysis showed a significant effect on knowledge of dental and oral hygiene. P. value = 0,000 and tooth brushing skills. P. value = 0,000 for inpatients in internal medicine wards with dental and oral nursing care. Conclusion: There is an effect of dental and oral nursing care on knowledge of oral hygiene and tooth brushing skills in inpatients in the internal disease ward at Bayu Asih Hospital, Purwakarta.